2020
DOI: 10.1007/s00520-020-05310-6
|View full text |Cite
|
Sign up to set email alerts
|

Guideline concordant care for prevention of acute chemotherapy-induced nausea and vomiting in children, adolescents, and young adults

Abstract: Purpose: Prescribing guideline-recommended anti-emetics is an effective strategy to prevent CINV. However, the rate of guideline-concordant care is not well-understood. The purpose of this study was to describe the proportion of pediatric, adolescent, and young adult patients receiving HEC or MEC who received guideline-concordant antiemetic prophylaxis for acute CINV, and to identify potential predictors of guideline-concordant antiemetic prophylaxis. Methods:Using electronic health record data from 2016 throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…In this study, low rates of adherence to the NCCN guideline were found, similar to what was reported by other authors who assessed agreement with the guidelines for prophylaxis of CINV. [7][8][9][10] In the study by Beauchemin et al, although they included only young patients using antineoplastic agents of moderate and high emetogenic potential, only 36.1% of them received antiemetic therapy according to international guidelines. 7 Nikbakht et al also found a low rate of adherence to the guidelines, especially for the protocols of moderate and high emetogenicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, low rates of adherence to the NCCN guideline were found, similar to what was reported by other authors who assessed agreement with the guidelines for prophylaxis of CINV. [7][8][9][10] In the study by Beauchemin et al, although they included only young patients using antineoplastic agents of moderate and high emetogenic potential, only 36.1% of them received antiemetic therapy according to international guidelines. 7 Nikbakht et al also found a low rate of adherence to the guidelines, especially for the protocols of moderate and high emetogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10] In the study by Beauchemin et al, although they included only young patients using antineoplastic agents of moderate and high emetogenic potential, only 36.1% of them received antiemetic therapy according to international guidelines. 7 Nikbakht et al also found a low rate of adherence to the guidelines, especially for the protocols of moderate and high emetogenicity. 8 Bun et al found agreement rates ranging from 21.5% to 52%, depending on the degree of emetogenicity of the protocol in use and on the age range of the patients.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 45–61% of cancer patients suffer from chemotherapy-induced nausea and vomiting (CINV). In antiemetic prophylaxis during chemotherapy, the following are used: (i) drugs from the group of 5-HT 3 receptor antagonists—ondansetron, granisetron, tropisetron, dolasetron, palonosetron; (ii) drugs from the group of neurokinin-1 receptor antagonists—aprepitant; (iii) corticosteroids—the most commonly recommended dexamethasone or methylprednisolone; and (iv) complementary drugs: dopamine receptor antagonists (metoclopramide), phenothiazine derivatives (chlorpromazine), antihistamines, and butyrophenone derivatives (haloperidol and droperidol) [ 112 ]. The guidelines propose the use of antiemetic drugs in monotherapy or according to a schedule of two-to-three drugs, depending on the degree of risk of nausea and vomiting and the individual sensitivity of the patient.…”
Section: Pharmacological Applicationmentioning
confidence: 99%
“…25,26 In fact, we recently reported that patients receiving emetogenic chemotherapy with commercial insurance were significantly more likely to receive guidelineconcordant antiemetic prophylaxis compared with those with Medicaid (odds ratio [OR]: 2.4; 95% confidence interval [95% CI]: 1.0-4.8). 19 All available EHR data from the first clinical encounter for HEC were included for each eligible patient.…”
Section: Samplementioning
confidence: 99%